THE INFLUENCE OF SHOP SCENE AND SALES PROMOTION ON PURCHASE DECISIONS ON RAMAYANA DEPARTMENT STORE IN SERANG - Guruh Ramadhan; Udin Bahrudin (AMAL INSANI (Indonesian Multidiscipline of Social Journal), 2020)
This study aims to determine the influence of store atmosphere on consumer purchasing decisions, to determine the effect of sales promotion on consumer purchasing decisions and to determine the effect of store atmosphere and sales promotion of consumer purchasing decision Ramayana Department Store in Serang City. This research uses quantitative research method, quantitative research method can be interpreted as research method based on positivism philosophy, used to research on population or certain sample, sampling technique generally done by random, data collection using research instrument, data analysis is quantitative / Statistics with the aim to test the hypothesis set. The population in this study is the consumer or visitors Ramayana Serang who ever made a purchase in Ramayana Serang City.   The method of determining the sample using the method suggested by Hair et al. (2006: 741) in Widikusyanto (2014) that the sample size required for factor analysis is at least five times the number of variables observed, so the sample used in this study is 5 times the number of indicators or statements totaling 26 items (5 x 26), so the sample size is 5 x 26 = 130, to avoid the questionnaire that is not complete or not returned, then the sample size plus 20, so the total sample is 150 respondents.  The results of hypothesis testing 1 shows the store atmosphere significantly influence consumer purchasing decision Ramayana Department Store in Serang City in this case if the store atmosphere increases then the decision will increase. The results of hypothesis testing 2 shows sales promotion significantly influence consumer purchasing decision Ramayana Department Store in Serang City in this case if sales promotion increases then the decision will increase. The result of hypothesis 3 shows store atmosphere and sales promotion significantly influence consumer purchasing decision Ramayana Department Store in Serang City, this matter if store atmosphere and promotion of sale increase then consumer purchasing decision will increase.